(untitled) (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
EDITOR-in-CHIEF Abdul Salam @ Zulkifli B.Muhamad Shukri (International Islamic University Malaysia) ASSOCIATE EDITOR Homam Altabaa (International Islamic University Malaysia) COPY EDITOR Kamel Ouinez (International Islamic University Malaysia) EDITORIAL ADVISORY BOARD Local Members Abdel Aziz Berghout (IIUM) Badri Najib bin Zubir (IIUM) Hassan Ibrahim Hendaoui (IIUM) Jamal Badi (IIUM) Muhammed Mumtaz Ali (IIUM) Rahmah Bt. Ahmad H. Osman (IIUM) Sayed Sikandar Shah (IIUM) Thameem Ushama (IIUM) Wan Mazwati Wan Yusoff (IIUM) Nadzrah Ahmad (IIUM) Saidatolakma Mohd Yunus (IIUM) International Members Abu Bakr Rafique (IIUC, Islamic International University Chittagong, Bangladesh) Fikret Karcic (University of Sarajevo, Bosnia) Israr Ahmad Khan (Fatih Sultan Mehmet Waqf University, Turkey) Muhammad Al-Zuhayli (University Of Sharjah, UAE) Muhammad Elamin Musa (Qater University) Saheed Ahmad Rufai (Sokoto State University, Nigeria)